IMPLEMENTASI FATWA MUI NOMOR 14 TAHUN 2020 Tentang Penyelenggaraan Ibadah Dalam Situasi Terjadinya Wabah Covid-19 di Kota Medan. - Dhiauddin Tanjung; Ramadhan Syahmedi; Gatot Teguh Arifyanto (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2021)
This study explains the MUI Fatwa Number 14 of 2020 which discusses the Implementation of Worship in the situation of the Covid-19 Outbreak in Medan City. This study also analyzes the MUI fatwa number 14 of 2020. This type of research includes empirical legal research and also includes field research. The approach used is an approach using laws and also a conceptual approach. The sources used in this study are the primary sources, namely the Qur'an and Hadith and the secondary sources are primary legal materials and the principles of fiqh and MUI fatwa no. 14 of 2020 concerning the Implementation of Worship during the Covid-19 period. The collection techniques are interviews, observations and documentation studies. The results of his research, namely the Implementation of the MUI Fatwa Number 14 of 2020 concerning the implementation of worship in the situation of the Covid-19 outbreak in the city of Medan, are still not effective, because based on the interview the author found that the results of several mosques in the city of Medan only accepted the MUI Fatwa appeal but did not carry out the completely as directed by the fatwa, they consider the fatwa only an appeal.